The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s40479-021-00157-7
|View full text |Cite
|
Sign up to set email alerts
|

Body connection mediates the relationship between traumatic childhood experiences and impaired emotion regulation in borderline personality disorder

Abstract: Background Previous studies revealed an association between traumatic childhood experiences and emotional dysregulation in patients with borderline personality disorder (BPD). However, possible mediating pathways are still not fully understood. The aim of the present study was to investigate the potential mediating role of body connection, describing the awareness of the relationship of bodily and mental states, for the association between a history of traumatic childhood experiences and BPD co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 77 publications
2
15
0
2
Order By: Relevance
“…Their generators are located in the anterior insula and dorsal anterior cingulate cortex (Pollatos et al, 2005)-and thus, in regions important for the integration and awareness of bodily signals (Critchley et al, 2004). Two independent studies have reported reduced resting-state heartbeat-evoked potentials in patients with BPD compared with healthy volunteers (Müller et al, 2015;Schmitz et al, 2020), in line with the reduced self-reported body awareness (Schmitz et al, 2021). Interestingly, no significant difference in the amplitude of heartbeat-evoked potentials could be found between patients with a former diagnosis of BPD and healthy volunteers (Müller et al, 2015), which may suggest plasticity in self-awareness related to symptom amelioration.…”
Section: Impairments In Self-awarenessmentioning
confidence: 96%
“…Their generators are located in the anterior insula and dorsal anterior cingulate cortex (Pollatos et al, 2005)-and thus, in regions important for the integration and awareness of bodily signals (Critchley et al, 2004). Two independent studies have reported reduced resting-state heartbeat-evoked potentials in patients with BPD compared with healthy volunteers (Müller et al, 2015;Schmitz et al, 2020), in line with the reduced self-reported body awareness (Schmitz et al, 2021). Interestingly, no significant difference in the amplitude of heartbeat-evoked potentials could be found between patients with a former diagnosis of BPD and healthy volunteers (Müller et al, 2015), which may suggest plasticity in self-awareness related to symptom amelioration.…”
Section: Impairments In Self-awarenessmentioning
confidence: 96%
“…[46,47] Social/Emotional Impairment This can range from mild social interaction issues to trauma-associated body disassociation. [48,49] Elevated risk of suicide This often co-occurs with major depressive disorder. [50,51] HPA axis dysregulation This recent review describes a neuroimmune regulation model for the resulting HPA hyperactivity.…”
Section: Conditions/attribute Details Referencesmentioning
confidence: 99%
“…In a recent study, female patients with BPD reported significantly lower levels of body awareness and significantly higher levels of body dissociation compared to healthy women. Significant positive correlations between body dissociation, traumatic childhood experiences, and emotion regulation were found [ 67 ].…”
Section: Dissociation In Borderline Personality Disorder (Bpd)mentioning
confidence: 99%